Single‐port laparoscopic incisional hernia repair in a horse. (17th February 2016) - Gandini, M.; Giusto, G.; Caramello, V.; Comino, F.; Rosso, A.
Summary: A 16‐year‐old Italian Saddle Horse gelding was referred for treatment of an incisional hernia that developed 7 months after a ventral midline laparotomy for treatment of acute abdominal pain. Physical examination revealed a hernia approximately 20 cm long and 15 cm wide on the ventral aspect of the abdomen. Ultrasonography revealed the dimensions of the hernia ring to be approximately 15 cm in length and 10 cm in width. A single‐port laparoscopic incisional hernia repair using an operating 0° laparoscope was performed with an appropriately sized (24 × 18 cm) piece of mesh fixed in place with simple interrupted transabdominal sutures. At 4 weeks post operatively, follow‐up physical examination and ultrasonography confirmed healing of the surgical site with no evidence of hernia recurrence. The same evaluation was done 6 months post operatively, and the horse returned to its previous level of activity 8 months post operatively. In horses, laparoscopic application of mesh should be considered among the treatment options for incisional hernia. In the present case, this technique was performed with a single port using an operative laparoscope, in contrast to the multiportal techniques reported previously. The case presented here demonstrates that single‐port laparoscopic herniorrhaphy is feasible, and allows proper placement of an expanded polytetrafluoroethylene intraperitoneal mesh in horses